Overexpression of tousled-like kinase 2 predicts poor prognosis in HBV-related hepatocellular carcinoma patients after radical resection - Liu, Bang; Lu, Ling-Ling; Yu, Li; Mei, Xuan; Liu, Jia; Zheng, Jiao-Long; Zhou, Xiao-Ling; Lin, Hai-Yan; Zhu, Xiu-Ling; Li, Dong-Liang (Frontiers in Genetics, 2024)
Background: Tousled-like kinase 2 (TLK2) is integral to DNA repair, replication, and cell cycle regulation, crucial for maintaining genome stability and integrity. However, the expression and prognostic value of TLK2 in hepatitis B viral (HBV) -related hepatocellular carcinoma (HCC) remains unclear. Methods: We examined TLK2 expression and prognostic implications in pan-cancer by using diverse databases. Subsequently, TLK2 expression in HBV-related HCC tissues and adjacent tissues was assessed using quantitative real-time PCR and immunohistochemistry. The prognostic value of TLK2 was assessed through ROC curves, time-dependent ROC curves, Cox regression, Kaplan-Meier curve, and decision curve analysis. Additionally, analyses of immune infiltration, protein-protein interactions, key molecules of tumor-related signaling pathways, molecular subtypes, and TLK2-associated differentially expressed genes (DEGs) were conducted, along with GO/KEGG and GSEA enrichment analyses. Results: TLK2 expression was significantly higher in HCC tissues compared to adjacent tissues, and correlated with gender, AFP levels, albumin-bilirubin (ALBI) grade, microvascular invasion (MVI), maximum tumor diameter, tumor number, and TNM stage. TLK2 overexpression emerged as an independent risk factor for overall survival (OS) and recurrence-free survival (RFS) in HBV-related HCC patients. An integrated OS nomogram model, incorporating TLK2, age, ALBI grade, MVI, and tumor number, displayed enhanced prognostic capability (C-index: 0.765, 95% CI: 0.732-0.798) in predicting OS and has a higher net benefit than the TNM stage. Moreover, TLK2 expression correlated closely with immune cell infiltration and key molecules of signaling pathways. Functional enrichment analyses highlighted significant associations with DNA duplex unwinding, double-strand break repair, DNA replication, cell cycle, E2F targets, G2M checkpoint, and MYC targets V1. Conclusions: TLK2 is notably overexpressed in HBV-related HCC and emerges as a promising prognostic biomarker, necessitating further validation.